Immunohistochemical investigation of vascular endothelial growth factor during the healing of gastric ulcer in female rats: experimental study - Jawad Al-Kawaz, Jenan Mahdi; Al-Zubaidy, Fakhir Magtoof; Obaid Al-Harbi, Hussein Jasim (Pharmakeftiki, 2025)
The current study attempts to characterize the effects of esomeprazole, curcumin, chitosan, as well as of a mixture of curcumin and chitosan on the expression of the vascular endothelial growth factor (VEGF) in gastric ulcers induced by ethanol in female rats. This study included 30 rats; their average weight ranged between 195.6 and 198.6 g, and the rats were separated into two control groups (negative and positive control groups) and four treatment groups (n=5 rats per group). All groups were treated for 5 days after last administration of distilled water or ethanol. The immunohistochemical staining for VEGF in the cells of gastric mucosa revealed a positive staining in both the control groups and all treated groups. The H-score for VEGF was found to exhibit no significant change (p>0.05) in any of the assessed groups.